Rescue therapy with C1-esterase inhibitor concentrate after emergency coronary surgery for failed PTCA - Bauernschmitt, Robert; Hagl, Siegfried; Böhrer, Hubert (Intensive care medicine, 1998)
Administration of C1-esterase inhibitor (C1-INH) attenuates myocardial necrosis and sustains normal cardiac performance after myocardial ischemia and re-perfusion in animal experiments. We report on our first experience of C1-INH application as rescue therapy in patients undergoing emergency surgical revascularization after failed percutaneous transluminal coronary angioplasty. Three patients were treated, because postoperative hemodynamic stabilization could not be achieved despite prolonged reperfusion periods, high-dose inotropic support, inodilators and aortic counterpulsation. As there was no surgical or medical option remaining, C1-INH was administered starting with a 2000 unit bolus, followed by 1000 U 12 and 24 h after surgery. C1-INH therapy resulted in rapid hemodynamic stabilization of all patients; weaning from aortic counterpulsation and epinephrine support was possible within 1 day. All patients survived and were discharged from hospital. In this group of patients suffering from severe reperfusion injury after coronary surgery, C1-INH seemed to be an effective adjuvant therapy to restore myocardial function by blocking the complement cascade. These results should encourage the performance of controlled studies on the effects of prophylactic C1-INH substitution therapy in patients undergoing coronary surgery at high risk conditions.